2014
DOI: 10.1371/journal.pone.0113857
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Disease and Ankle-Brachial Index Abnormalites in Young and Middle-Aged HIV-Positive Patients in Lower Silesia, Poland

Abstract: BackgroundPeripheral arterial disease (PAD) is a clinical manifestation of atherosclerosis and mainly refers to elderly patients, having a negative impact on their functionality and quality of life. The findings of previous studies in HIV-infected patients have shown that cardiovascular risk is higher and PAD occurs more frequently than in the general population. There are also contradictory observations. Much less is known about the ankle-brachial index (ABI) value in asymptomatic HIV-infected patients. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…However, studies have been inconsistent on whether the prevalence of PAD in HIV+ populations is higher or lower than in the general population [7981]. Recent studies have shown low prevalence of PAD as measured by ABI in HIV+ populations that is similar to the prevalence in the general population [82, 83]. More importantly, ABI in HIV+ patients was not correlated with CIMT or traditional risk factors for CVD [83].…”
Section: Vascular Diseasesmentioning
confidence: 99%
“…However, studies have been inconsistent on whether the prevalence of PAD in HIV+ populations is higher or lower than in the general population [7981]. Recent studies have shown low prevalence of PAD as measured by ABI in HIV+ populations that is similar to the prevalence in the general population [82, 83]. More importantly, ABI in HIV+ patients was not correlated with CIMT or traditional risk factors for CVD [83].…”
Section: Vascular Diseasesmentioning
confidence: 99%
“…A Spanish study reported a 10 times higher prevalence of PAD in HIV‐infected patients aged > 50 years than in age‐matched healthy persons who came to hospital for their annual check‐up (10 versus 1%, respectively) . An estimated 7.3% of HIV‐infected patients with a median age of 42 years had abnormal ABI in a Polish study (median time on ART 6 years) versus none in the HIV‐negative control group .…”
Section: Discussionmentioning
confidence: 99%
“…The same study population was analyzed in our previous publications [28]. The preliminary inclusion criteria were: documented HIV infection and antiretroviral therapy, of no less than 2 years.…”
Section: Methodsmentioning
confidence: 99%